Fakulti gemilang, graduat terbilang - Ismail, Issham (Faculty of Chemical & Natural Resources Engineering, 2008)
This was the welcoming speech addressed by the Director of FKKKSA's 25th Anniversary Celebration. The grand celebratory dinner was officiated by the Vice-Chancellor of Universiti Teknologi Malaysia, Tan Sri Professor Dr. Mohd. Zulkifli bin Tan Sri Mohd. Ghazali, and attended by the UTM's top management, FKKKSA’s management, FKKKSA’s staff and ex-staff, alumni, and representatives from oil and gas industries, Dow Chemicals, JKJ, etc. The theme of the grand celebratory dinner was ‘Fakulti Gemilang, Graduat Terbilang’. In the same event, the 25th anniversary book entitled ‘Menganjak ke Persada Dunia’ was also launched.